Chronic depression treated successfully with novel taping therapy: a new approach to the treatment of depression - Han CH (Dove Medical Press, 2016)
Chang Hyun Han,1,* Hwa Soo Hwang,2,* Young Joon Lee,3 Sang Nam Lee,4 Jane J Abanes,5 Bong Hyo Lee6 1Clinical Research Division, Korea Institute of Oriental Medicine, Daejeon, 2Chims-Saengvit Oriental Medicine Clinic, Seoul, 3Department of Preventive Korean Medicine, 4Department of Qigong, College of Korean Medicine, Daegu Haany University, Gyeongsangbuk-do, South Korea; 5Daniel K Inouye Graduate School of Nursing, Uniformed Services University of the Health Sciences, Bethesda, MD, USA; 6Department of Acupuncture, Moxibustion and Acupoint, College of Korean Medicine, Daegu Haany University, Daegu, South Korea *These authors contributed equally to this work Introduction: Despite improved research in the treatment, depression remains difficult to treat. Till date, successful treatment of depression using taping therapy has not been known yet. We report cases where patients with severe depressive symptoms were successfully treated by taping therapy, a new approach.Methods: In case 1, a patient was taking several psychiatric medications for 10 years and admitted often to the psychiatric hospital with a leaning head, flexible legs, and nearly closed eyes; in case 2, a patient after a hysterectomy complained with heart palpitations, depressive- and anxiety-like behaviors, insomnia, and gastrointestinal problems; and in case 3, a patient with complaints of adverse effects from antidepressant medications had suicidal thoughts frequently. The medical tapes were placed on acupoints, trigger points, and pain points found by finger pressing examination in the chest, sides, and upper back of the patients.Results: In case 1, the patient started weeping immediately after the first treatment. He discontinued psychiatric drugs and returned to baseline functioning after 2 months. In case 2, the patient felt at ease showing decreased palpitation immediately after the first treatment, and after 1 week, she quit medications. In case 3, the patient experienced a sense of calmness following the first treatment and recovered from her symptoms after 2 weeks.Conclusion: These results suggest the following key points: examination of acupoints and trigger points of chest, sides, and upper back is useful in the assessment of depression; regulating bioelectric currents on these points is helpful in the treatment of depression; and depression can be treated successfully with taping therapy. Keywords: fatigue, insomnia, bioelectricity, bioelectric current, acupoint, trigger point